Non-Newtonian Cross fluid flow through a porous medium with regard to the effect of chemical reaction and thermal stratification phenomenon. (January 2022) - Megahed, Ahmed M.; Abbas, W.
Abstract: A comprehensive study encompassing a general development and a presentation of results for the influence of the chemical reaction on the laminar Cross fluid flow and heat mass transfer is made here. The motion of the fluid is assumed due to the stratified stretching sheet which embedded in a porous medium. Some of important characteristics of the fluid such as the variable thermal conductivity and its dependence on the temperature field are mentioned. Accordingly, some account of the possible effects of heat generation on heat mass transfer in fluid flows is given. Numerical treatments have been introduced for the resulting coupled ordinary differential equations. Then, the results of the variation in the velocity profile, the temperature profile and the concentration profile due to porous parameter, thermal conductivity parameter, heat generation parameter, thermal stratification parameter and chemical reaction parameter are presented graphically. At the proposed physical conditions for the problem, the Sherwood number, the Nusselt number or the temperature gradient and the local skin friction coefficient were measured. It is interesting to observe that, both the solutal and the thermal stratification phenomena plays a dominant role in the mechanism of heat and mass transfer. Also, regarding the warming factors within the thermal boundary layer, both Darcy parameter and heat generation parameter have been proposed which are of special interest in heat transfer problems. Finally, the results pointed out the efficiency of the proposed numerical method, where it gives a good representation describing the mechanism of the flow, heat and mass transfer.